Research Trends and Knowledge Networks of SME in the Visegrád Group (V4) Countries: a Bibliometric Exploration - Talukder, Saurav Chandra (Acta Carolus Robertus, 2024)
This paper provides a bibliometric study of the V4 countries’ small and medium-sized enterprise (SME) research patterns and knowledge networks. Using data (n=3383) from the Web of Science and Scopus database between 1990 and 2023, researcher examines Key features of SME research, such as publishing trends, influential sources and institutions, well-known authors, and conceptual structure of the literature. The research shows that there has been an uptick in scholarly articles focusing on small and medium-sized enterprises (SMEs) in recent years, especially in 2019. The top three journals by number of articles published are sustainability, Polish Journal of Management Studies and Journal of Thermal Analysis and Calorimetry. On the other hand, the most influential institutions are Jagiellonian University of Poland, Tomas Bata University Zlin of Czech Republic, University of Silesia in Katowice of Poland, Furthermore, researcher employs keyword maps, thematic maps, and conceptual structure maps to uncover recurrent themes like impact of SMEs, SME finance, performance management, and gender inclusivity of SMEs. This study has important implications for policymakers, researchers, and practitioners who are interested in fostering the growth and innovation of small and medium-sized enterprises (SMEs) in the V4 countries.